Research on Energy Scheduling Strategy of DC Microgrid with Multiple Power Routers - Tang, Shujian; Zhang, Meng; Zhu, Junjie (2024 IEEE 2nd International Conference on Control, Electronics and Computer Technology (ICCECT), 2024)
The DC microgrid clusters have become one of the main networking forms for residential and industrial parks in the future due to its simple control method and high DC load and distributed energy consumption efficiency. This paper takes the low-voltage DC microgrid clusters as the research object. First, it gave the matching and scheduling method of the top-level control, and then designed a DC microgrid clusters experimental device to complete the communication and dispatch experiment. In the first stage, a packetized power dispatch protocol was proposed and the matching and power transmission dispatch are expressed as two problems respectively. In the matching problem, a mixed-integer nonlinear programming algorithm is better than a one-to-one matching algorithm in terms of matching efficiency, and it has obvious advantages in dealing with power line transmission loss. However, the greater time complexity ( o (2 S × D+D )) of the mixed-integer nonlinear programming algorithm than that (o(SD)) of the latter leads to longer matching time. In the scheduling problem, the heuristic algorithm performs better than the knapsack algorithm under the number of multi-power channels. In the second stage, a dispatch platform was designed for experimental verification. The four-cycle continuous scheduling experiment verified the correctness of the scheduling protocol.